Being forgotten, being remembered: The affective politics of Waiwai memory in Guyanese Amazonia. (20th July 2022) - OAKLEY, R. ELLIOTT
ABSTRACT: In the Guyanese Amazon, Waiwai memory is made through the substances and associated sentiments that accrue in the body. Remembering and forgetting are morally weighted actions that transform the dispositions of others, enabling desired feelings of contentment or anger and ill will. Waiwai perspectives on the stakes of being or not being in the thoughts of others matter for their relations with the state: Waiwai people say that, in the past, their households were split between Guyana and Brazil because the Guyanese government forgot about them, while in the present, Waiwai people work to make Guyanese officials remember them, and this constitutes a form of political practice. Whereas anthropological accounts of the politics of memory emphasize how the past is operationalized in the present, Waiwai discussions of being forgotten and being remembered demonstrate the significance of affective, rather than representational, forms of memory for the political practices of indigenous‐state relations. [ memory, morality, politics, affect, Waiwai, Guyana, Amazonia ]